The development of higher education in Japan and the United Kingdom: The impact of neoliberalism. (15th October 2020) - Brazzill, Marc
Abstract: There is a growing consensus in political science research that higher education systems are classifiable into stable distinct types that reflect dominant trends in government partisanship. There is also a large body of higher education research that argues that higher education systems are changing and converging upon a neoliberal type, which is not yet reflected in the political science literature. This paper seeks to reconcile these two positions by looking at both the development of higher education systems in the post‐war period and subsequent systemic reforms that have been identified as neoliberal. There have been two main targets of reform: (a) the role the state plays in funding and targeting research, and (b) student finance regimes consisting of tuition fees and the system of financial aid. This paper provides an in‐depth look at the cases of Japan and the United Kingdom, which developed into very different systems in the post‐war period but have since shown slight convergence on the back of neoliberal reforms. 概要: 政府の党派性により、高等教育制度を明確に分類できることが政治学では主流になった。ただし、様々な高等教育制度が一つの新自由主義型に収束している主張が高等教育学ではある。本稿の目的は、高等教育制度の戦後の発展とその後の新自由主義的な改革を検討し、この二つの研究アプローチを合併することである。本稿では、戦後に類似しなかったが近年の新自由主義的な改革で収束の傾向を表している日本とイギリスの事例を通し、研究の資金と目的に対しての政府の役割と、学費と奨学金支援制度を含む学生金融体制に対するその改革の影響を解明する。